Ultrasonic welding of novel carbon/Elium® thermoplastic composites with flat and integrated energy directors : lap shear characterisation and fractographic investigation - Bhudolia, Somen K. (2020)
The current research work presents a first attempt to investigate the welding attributes of Elium® thermoplastic resin and the fusion bonding using ultrafast ultrasonic welding technique. The integrated energy director (ED) polymer-matrix composites (PMCs) panel manufacturing was carried out using the Resin Transfer Moulding (RTM) technique and the scheme is deduced to manufacture a bubble-free panel. Integrated ED configurations and flat specimens with Elium® film of different thickness at the interface were investigated for ultrasonic welding optimization. Optimised weld time for integrated ED and flat Elium® panels with film (0.5 mm thick) configuration was found to be 1 s and 5.5 s, respectively. The ED integrated configuration showed the best welding results with a lap shear strength of 18.68 MPa. The morphological assessment has shown significant plastic deformation of Elium® resin and the shear cusps formation, which enhances the welding strength. This research has the potential to open up an excellent and automated way of joining Elium® composite parts in automotive, wind turbines, sports, and many other industrial applications.